2013
DOI: 10.4103/1658-354x.114058
|View full text |Cite
|
Sign up to set email alerts
|

Hemiarthroplasty in high risk elderly patient under epidural anesthesia with 0.75% ropivacaine-fentanyl versus 0.5% bupivacaine-fentanyl: Clinical trial

Abstract: Background:Anesthetic management of elderly patients is a challenge as aging makes them more susceptible to hemodynamic fluctuations during regional anesthesia. This study was aimed to compare the clinical efficacy of epidural 0.75% ropivacaine fentanyl (RF)– with 0.5% bupivacaine–fentanyl (BF) for hemiarthroplasty in high-risk elderly patients.Methods:Sixty elderly consented patients of either sex with American Society of Anesthesiologist ASA II and III, scheduled for elective hemiarthroplasty were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Also Bajwaet al 8 and Kamal, M. M. and Talaat, S. M. 17 found in their study that dry mouth was more common with epidural dexmedetomidine which we also found in our study. Also Selim MF et al 2 and Gupta et al 9 in their study foundthat the incidence of nausea and vomiting was higher in the fentanyl group than dexmedetomidine group, when given epidural injection which is in accordance to our findings. Similarly,Hanoura S, Hassanin R and Singh R. 18 and Bamne et al 16 in their study did not found any significant side effects by the addition of epidural dexmedetomidine and fentanyl.…”
Section: Side Effectssupporting
confidence: 92%
See 4 more Smart Citations
“…Also Bajwaet al 8 and Kamal, M. M. and Talaat, S. M. 17 found in their study that dry mouth was more common with epidural dexmedetomidine which we also found in our study. Also Selim MF et al 2 and Gupta et al 9 in their study foundthat the incidence of nausea and vomiting was higher in the fentanyl group than dexmedetomidine group, when given epidural injection which is in accordance to our findings. Similarly,Hanoura S, Hassanin R and Singh R. 18 and Bamne et al 16 in their study did not found any significant side effects by the addition of epidural dexmedetomidine and fentanyl.…”
Section: Side Effectssupporting
confidence: 92%
“…Table 21 shows the spo2 of both the groups. Appropriate statistical test shows that there was no significant difference in the above parameter in the two study groups, which corroborates with the findings of Oriol Lopez SA et al 15 , J. Carreon, et al 7 , Bajwaet al 8 , Yongxin Liang, et al 19 , Selim MF et al 2 , Gupta et al 9 , Negi S et al 14 and Bamne et al 16…”
Section: Hemodynamic Changes and Spo2supporting
confidence: 81%
See 3 more Smart Citations